O corpo-texto no corpo-feminino em Niketche: uma performance literária - Shimbo, Renata Vaz (2015)
This dissertative analysis of the Mozambican writer Paulina Chiziane's Niketche: a history of polygamy (2004) represents a reading about the novel the dialogical relationship between body and text. At first, the historical background in which the Portuguese language was inserted in Africa and, in this case, in Mozambique, is privileged. In this sense, it is verified that geographical and historical factors had determined the relationships established between society and the gender feminine in the country, as well as it led to a need for a reinvention for their cultural identity. The rewriting of female otherness is verified in the novel through Niketche s dance performance, through which the rhythmic movements synthesize eroticism and the desecration of a traditional ritual, subverting it into the female body s release instrument. Through the theoretical basis of thinkers like Zumthor (1985, 1993), Bakhtin (1977, 2002), Antonacci (2013) and Irobi (2007), it is argued that the dance sacred ritual in Niketche acquires body and text form, writing an utopic performance place for femal s voice and body of Mozambique